Determinants of bone mineral density and effect of soy isoflavones in premenopausal women in the Klang Valley, Malaysia - Tee, Yvonne Yee Siang (2013)
Isoflavones, a class of phytoestrogens or plant-derived compounds with estrogenic activity found abundantly in soybeans and soy products, are purported to have protective effects on bone health. A 12-month randomized-control trial was conducted to determine the determinants of bone mineral density and effect of soy isoflavones on bone mineral density (BMD) among 73 non-osteoporotic premenopausal Chinese women. The treatment group received 100 mg of soy isoflavones supplement daily containing approximately 43.09 mg (86.2%) of the isoflavones in aglycone form. Changes in BMD were assessed every 6 months using dual-energy X-ray absorptiometry (DEXA). Weight and height were measured using appropriate instrument and fat mass and lean mass were assessed by DEXA. Analysis on bone markers and several biochemical indicators such as lipid profile was carried out. Dietary intake and selected lifestyle variables were also assessed. At baseline, there was no significant difference between treatment and control group for their socioeconomic background, anthropometric measurements, dietary intake, biochemical parameters and physical activity level, except that the control group had higher baseline BMD at the Ward’s triangle compared to the soy isoflavones group (p<0.05). The mean age of the subjects was 39.3 ± 5.0 years. Their mean body mass index (BMI) was 22.2 ± 3.4 kg/m2 and their average body fat percentage and lean body mass were 33.9 ± 4.6% and 34.5 ± 4.4 kg, respectively. The mean BMD at the spine, total hip, femoral neck, and total body were 1.025 ± 0.118 g/cm2, 0.876 ± 0.109 g/cm2, 0.739 ± 0.110 g/cm2, and 1.061 ± 0.755 g/cm2, respectively. The mean caloric and calcium intake were 1506 ± 427 kcal / day and 534 ± 347 mg / day, respectively. Their calcium intake only achieved 66.8% of the Recommended Nutrient Intake (RNI) of Malaysia. The mean metabolic equivalent score (MET) was 771.4 ± 926.1 min / week. On average, the serum levels of most biochemical indicators such as glucose, lipid profile, calcium, phosphorus, and magnesium were within normal range. Mean serum parathyroid hormone (PTH) was 36.1 ± 18.2 pg/ml;while mean serum beta-crosslaps was 0.21 ± 0.10 ng/ml. Conversely, mean serum osteocalcin (8.5 ± 4.2 ng/ml) was lower than the reference value. Age at menarche was negatively correlated with BMD at the femoral neck (r=-0.243,p<0.05). Body weight and its related indices (BMI, lean mass, fat mass) were significantly correlated with BMD at all skeletal sites. None of the dietary and physical activity factors were associated with BMD at various sites. Using the repeated measure ANOVA analysis, soy isoflavones supplementation had no effect on changes in BMD at all skeletal sites after 12 months. The findings of the study did not show any significant gain or loss in BMD from baseline in both the supplemented and control groups. Similarly, dietary intake, biochemical indicators and physical activity did not change significantly with time and between soy isoflavone and control group. In conclusion, daily supplementation with 100 mg of soy isoflavones did not show a bone-sparing effect in healthy premenopausal women. Although the soy isoflavones tablets in this study were well-tolerated and did not result in any adverse effects, the long-term safety of very high supplemental doses of soy isoflavones is not yet known. Therefore, consumption of diets rich in soy and soy products may be the preferred option to gain the beneficial effects of isoflavones on bone health in both premenopausal and postmenopausal women.